Aircel Crisis: Disruptive Competition or Corruption– What Next?. Issue 3 (September 2019) - Aggrawal, Artee
Abstract: Even though the emerging economies are growing with a fast pace, they have their own problems like growing population, corruption low per capita income and low purchasing power. India has its considerable dynamics like lower middle-class consumers, price competition, disruptive technologies and corruption. The present case study is about a struggling player of telecom industry in India. The telecom sector of India is an oligopoly market with only few dominant players. Entry of Relience-Jio in the year 2016 disrupted the market and making it difficult for all well-established companies to stay afloat. Aircel India, once a poster boy of Indian telecom sector, finds itself into intensive competition and numerous corruption charges. The case presents an opportunity in front of the students to evaluate a series of difficult decisions, all of which require trade-offs in the interest of keeping the company afloat. The case is developed by the data collected using unobtrusive methods from newspaper articles and research reports on the topic.